RESOURCE BASED VIEW DALAM KERANGKA MODEL STRATEGIC MANAGEMENT - Arif Sugiono (AdBispreneur : Jurnal Pemikiran dan Penelitian Administrasi Bisnis dan Kewirausahaan, 2018)
This research aims to break down the scientific roots of the resource based view within the framework of the strategic management model, which is at the first element in the strategic management model, namely environmental scanning. To answer these objectives, a literature review method is used. The results of the study show that the strategic management model was born from a modern approach in the evolution of the development of organizational theory. As a consequence, the strategic management model must place a balance between internal strength / resource based view and the external environment / market based view in designing the strategy. While the resource based view, was born from several basic concepts developed from classical economists. Further theoretical and empirical studies of the critical review of the strategic management model are needed in the midst of increasingly disruptive environmental dynamics.Studi ini bertujuan ingin mengurai akar keilmuan dari resource based view dalam kerangka model strategic management, yang berada pada elemen pertama dalam model strategic management, yakni environmental scanning. Untuk menjawab tujuan tersebut, digunakan metode kajian pustaka. Hasil kajian menunjukkan, model strategic management lahir dari pendekatan modern dalam evolusi perkembangan teori organisasi. Sebagai konsekwensinya,  model strategic management harus menempatkan keseimbangan antara kekuatan internal/resource based view dan eksternal/ market based view dari organisasi dalam mendesain strategi. Sedangkan resource based view, lahir dari beberapa konsep dasar yang dikembangkan dari para pemikir ekonom klasik.  Diperlukan kajian lanjutan yang bersifat teoritis dan empiris tentang tinjauan kritis model strategic management ditengah dinamika lingkungan yang semakin disruptif.